2021
DOI: 10.3390/nano11020373
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of PDMS-Like Polymer Nanocomposites with Enhanced Thermal Conductivity: Boron Nitride Based Photocuring System

Abstract: This study demonstrates the possibility of forming 3D structures with enhanced thermal conductivity (k) by vat printing a silicone–acrylate based nanocomposite. Polydimethylsiloxane (PDSM) represent a common silicone-based polymer used in several applications from electronics to microfluidics. Unfortunately, the k value of the polymer is low, so a composite is required to be formed in order to increase its thermal conductivity. Several types of fillers are available to reach this result. In this study, boron n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
(78 reference statements)
2
27
0
Order By: Relevance
“…Unlike the neat formulation (F0), all the doped formulations (referred to as FX, where X is the concentration of CNTs in wt.%) show a typical shear‐thinning behavior (Figure S1, Supporting Information), in good accordance with previous reports on resins embedding nanofillers. [ 44,45 ] Further, as becomes clear from the values reported in Table 1, the higher the content of CNTs, the higher the viscosity of the formulations since the interaction between the CNTs limits the mobility of the polymer chains. However, according to the literature, such viscosity values are acceptable for DLP‐Printing.…”
Section: Resultsmentioning
confidence: 98%
“…Unlike the neat formulation (F0), all the doped formulations (referred to as FX, where X is the concentration of CNTs in wt.%) show a typical shear‐thinning behavior (Figure S1, Supporting Information), in good accordance with previous reports on resins embedding nanofillers. [ 44,45 ] Further, as becomes clear from the values reported in Table 1, the higher the content of CNTs, the higher the viscosity of the formulations since the interaction between the CNTs limits the mobility of the polymer chains. However, according to the literature, such viscosity values are acceptable for DLP‐Printing.…”
Section: Resultsmentioning
confidence: 98%
“…Initially, samples without PETMP (tetrathiol) were irradiated under ambient conditions with a red LED centered at 617 nm (full width at half maximum (FWHM) ≈ 19 nm) having an intensity of 2.5 mW cm −2 (matching the DLP 3D printer intensity). For context, commercial UV/violet-light DLP 3D printers that operate at 385-405 nm have reported intensities exceeding 10 mW cm −2 , [38][39][40][41][42][43] which is significantly higher than the present system and represents a future avenue to examine for improved printing speed and resolution. Red LED illumination resulted in an inhibition period of 49.4 ± 0.4 s and an initial rate of polymerization of 7.5 ± 5.3% s −1 (immediately following inhibition) (Figure 3a and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Other nanoparticles are, for example, silica, which have given greater thermoelasticity, increased handling and performance quality of thermoplastic polymers, or polyhedral oligomeric silsesquioxane (POSS) nanoparticles, that have increased flexural strength (22%), flexural modulus (9%) and toughness (117%), compared to pure PLA [ 85 ]. Furthermore, Pezzana et al 2021 demonstrated the possibility of increasing the thermal conductivity and thermal conductivity of a silicon-acrylate nanocomposite using boron nitride (BN) nanoparticles [ 90 ].…”
Section: Materials For Fff Technologymentioning
confidence: 99%